Service learning in South Africa: lessons learnt through systematic evaluation - Mouton, Johann; Wildschut, Lauren (Acta Academica: Critical views on society, culture and politics, 2005)
This article is based on an evaluation report written for JET Education Services and covers a two-year period of an evaluation study of service learning courses (or modules) at five higher education institutions in South Africa. The article explores various models of service learning and considers the critical conditions for effective conceptualisation and delivery of a service learning course within an academic course. It also examines some of the key factors involved in the institutionalisation of service learning so that this form of community engagement can become a sustained and viable element of the normal academic offerings of South African higher education institutions.